Auxin and Tryptophan Homeostasis Are Facilitated by the ISS1/VAS1 Aromatic Aminotransferase in Arabidopsis. Issue 1 (10th July 2015) - Pieck, Michael; Yuan, Youxi; Godfrey, Jason; Fisher, Christopher; Zolj, Sanda; Vaughan, Dylan; Thomas, Nicholas; Wu, Connie; Ramos, Julian; Lee, Norman; Normanly, Jennifer; Celenza, John L
Abstract: Indole-3-acetic acid (IAA) plays a critical role in regulating numerous aspects of plant growth and development. While there is much genetic support for tryptophan-dependent (Trp-D) IAA synthesis pathways, there is little genetic evidence for tryptophan-independent (Trp-I) IAA synthesis pathways. Using Arabidopsis, we identified two mutant alleles of ISS1 ( I ndole S evere S ensitive ) that display indole-dependent IAA overproduction phenotypes including leaf epinasty and adventitious rooting. Stable isotope labeling showed that iss1, but not WT, uses primarily Trp-I IAA synthesis when grown on indole-supplemented medium. In contrast, both iss1 and WT use primarily Trp-D IAA synthesis when grown on unsupplemented medium. iss1 seedlings produce 8-fold higher levels of IAA when grown on indole and surprisingly have a 174-fold increase in Trp. These findings indicate that the iss1 mutant's increase in Trp-I IAA synthesis is due to a loss of Trp catabolism. ISS1 was identified as At1g80360, a predicted aromatic aminotransferase, and in vitro and in vivo analysis confirmed this activity. At1g80360 was previously shown to primarily carry out the conversion of indole-3-pyruvic acid to Trp as an IAA homeostatic mechanism in young seedlings. Our results suggest that in addition to this activity, in more mature plants ISS1 has a role in Trp catabolism and possibly in the metabolism of other aromatic amino acids. We postulate that this loss of Trp catabolism impacts the use of Trp-D and/or Trp-I IAA synthesis pathways.